Development high yielding, good qualitative winter wheat cultivar (Triticum aestivum L.) Myrlyena - О. М. Черемха (Plant Varieties Studying and Protection)
The article presents agronomic and biological characteristics of new winter wheat cultivar Myrlyena. Pedigrees of its components of crossing are given.